The Effect of Burned Rice Husks and NPK Fertilizer Application on The Growth of Bok Choy (Brassica Rapa L. Subsp. Chinensis) - Ranti Eka Lestari; Lalu Zulkifli; Ahmad Raksun (Jurnal Biologi Tropis, 2023)
Fertilizer is very important factor in achieving high productivity, especially in providing essential nutrients. The application of inorganic fertilizers without adding organic fertilizers potentially reduces soil fertility and damages soil structure. This study aimed to determine the effect of burned rice husks, NPK fertilizer application, on the growth of Chinensis bok choy (Brassica rapa L. Subsp. Chinensis). The study employed a completely randomized design (CRD) consisting of 2 factors, with 5 treatment levels. The burned rice husks treatments comprised (0 gr, 90 gr, 110 gr, 130 gr, and 150 gr), while the NPK fertilizer treatments comprised (0 gr, 0.4 gr, 0.6 gr, 0.8 gr, 1.0 gr / 100 ml water). Data were analyzed using an ANOVA test. The results showed that the NPK fertilizer factor significantly influenced all parameters, including plant height, leaf number, wet weight, and dry weight. The burned rice husks factor and the interaction between burned rice husks and NPK fertilizer had no significant effect on all parameters, namely plant height, leaf number, wet weight, and dry weight of the Chinensis bok choy. The optimal treatment for the interaction of burned rice husks and NPK fertilizer "Mutiara 16" was with the N4S4 treatment (combination of NPK Mutiara 1.0 gr/100 ml water and burned rice husks 150 gr) for plant height, leaf number, wet weight, and dry weight parameters, while the optimal treatment for chlorophyll concentration content was with the N3S2 treatment (combination of NPK Mutiara 0.8 gr/100 ml water and burned rice husks 110 gr).